Peningkatan Organizational Citizenship Behavior Melalui Kompensasi dan Iklim Organisasi dengan Kepuasan Kerja sebagai Variabel Intervening - Aurelia Della Putri; Erni Yuningsih; Ismartaya Ismartaya (Universitas Katolik Widya Karya Malang, 2023)
Organizational Citizenship Behavior is behavior outside the tasks specified by the company that has a positive impact on the company. Given the magnitude of the influence of compensation, organizational climate and job satisfaction on organizational citizenship behavior, it is appropriate for companies to pay attention to this matter to run the company. This study aims to determine the effect of compensation and organizational climate on organizational citizenship behavior with job satisfaction as an intervening variable. The research method used is path analysis. The sample used in this research is all employees of PT. Jayamandiri Gemasejati Bogor, totaling 40 peoples. The results showed that simultaneously and partially the variables of compensation and organizational climate have a positive and significant effect on job satisfaction, simultaneously compensation, organizational climate and job satisfaction have a positive and significant effect on organizational citizenship behavior, partially compensation has no significant effect on organizational citizenship behavior, partially organizational climate and job satisfaction have a positive and significant effect on organizational citizenship behavior, job satisfaction is able to mediate compensation on organizational citizenship behavior, and job satisfaction is not able to mediate organizational climate on organizational citizenship behavior